Grain yield and yield components in synthetical cereals (tricepiros y triticales) (Semiárida, 2020)
In this work, the yield componentes of experimental lines of tricepiros and triticales with grain industial aptitude were analyzed as an indirect criterion of selection. The partition of the simple correlation between direct and indirect effects gives information on the functional relationship between components of different hierarchy and the end product. The number of tiller per plant showed a significant and direct effect over the grain yield. It is concluded that crosses between lines with high number of tillers, and triticales with adequate grain characteristics might increase the grain yield of tricepiros.
Keywords: triticales; tricepiros; yield components; grain yield per plant; path coefficient